2017
DOI: 10.1111/jcmm.13406
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer‐binding protein β overexpression alleviates myocardial remodelling by regulating angiotensin‐converting enzyme‐2 expression in diabetes

Abstract: Diabetic cardiomyopathy, a major cardiac complication, contributes to heart remodelling and heart failure. Our previous study discovered that CCAAT/enhancer‐binding protein β (C/EBPβ), a transcription factor that belongs to a family of basic leucine zipper transcription factors, interacts with the angiotensin‐converting enzyme 2 (ACE2) promoter sequence in other disease models. Here, we aimed to determine the role of C/EBPβ in diabetes and whether ACE2 expression is regulated by C/EBPβ. A type 1 diabetic mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Intriguingly, approximately 72% of targets anticipated to be up-regulated were confirmed to be elevated indeed in diseased conditions by previous reports, [40][41][42][43][44][45][46][47][48][49][50][51] and 50% of targets expected to be down-regulated were actually reduced. [52][53][54][55][56][57] This result proves that EV miRs from failing hearts substantially affect gene expressions in the heart.…”
Section: F I G U R Esupporting
confidence: 53%
“…Intriguingly, approximately 72% of targets anticipated to be up-regulated were confirmed to be elevated indeed in diseased conditions by previous reports, [40][41][42][43][44][45][46][47][48][49][50][51] and 50% of targets expected to be down-regulated were actually reduced. [52][53][54][55][56][57] This result proves that EV miRs from failing hearts substantially affect gene expressions in the heart.…”
Section: F I G U R Esupporting
confidence: 53%
“…For example, C/EBP‐β reduced fibronectin synthesis by regulating the transcription of TINag while the deficiency of C/EBP‐β aggravated renal fibrosis . In UUO‐induced renal fibrosis and STZ‐induced rat diabetic nephropathy, C/EBP‐β was notably decreased in fibrotic kidneys and contributes to ameliorate renal fibrosis . Although some study indicated that TGF‐β1 could upregulate C/EBP‐β in human lung fibroblasts, compelling evidence suggested that in primary renal tubular epithelial cells TGF‐β1 reduce C/EBP‐β expression .…”
Section: Discussionmentioning
confidence: 99%
“…Dependent on bioinformatics and IRF-1 transfection, we performed Human Klotho promoter analysis and focused on C/EBP-β which is a ubiquitously transcription factor belongs to C/EBPs family and affects expression of multiple genes by binding to their promoters. 39,50,51 Previous studies have shown that the transcription factor IRF-1 could form a function complex with other transcription factors to regulate gene expression in a cooperative manner. 52,53 However, it is unclear whether IRF-1 and C/EBP-β could interact physically each other to regulate the Klotho expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancer-binding protein β is a specific sequence CCAAT associated transcription factor which up-regulates of ACE2 expression by its overexpression. The transcription factor C/EBPβ also increased angiotensin (1–7) levels, but a less significant difference was determined ( Tie et al 2017 ).…”
Section: Regulatory Pathways Related To Ace2 Expressionmentioning
confidence: 97%